Digital Disruption: Empowering International Society Advocating Palestinian People Against Israeli Genocide - Munzilin, Khairul; Pertiwi, Elyana Ade (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
Israel's atrocities against the people of Palestine in Gaza have entered an unprecedented stage through acts of genocide. Moreover, America's partiality towards Israel has an impact on the reluctance of other state actors to intervene deeply. However, the behavior of state actors is inversely proportional to non-state actors (individuals). The international community strongly supports Gaza through digital disruption in influencing international politics. This research attempts to explain how digital disruption helps international society advocate for Palestinians in the genocidal act conducted by Israel. The main instrument used in this research is Transnational Advocacy Networks (TAN) by Margaret Keck and Kathryn Sikkink. This research used a qualitative-descriptive method with primary and secondary data. Findings of this research are: First, despite the positive and negative stigma, digital disruption contributes significantly to empowering non-state actors (individuals) in international politics. Second, digital disruption impelled non-state actors (individuals) to pressure state actors into an anarchic international order. Third, two significant phenomena (digital disruption and genocide) became supporting tools and drivers for the emergence of new strategic methods as advocacy efforts in the resistance movement. In general, this research sees that massive digital disruption has provided an opportunity for the international society (non-state actors) to fight for justice for the people of Palestine in Gaza for the occupation and genocide by Israel.